Alport syndrome: Expanding diagnosis and treatment - Hou-Xuan Huang; I-Jung Tsai; Larry A. Greenbaum (Pediatrics and Neonatology)
Alport syndrome (AS) is the second common monogenic cause of end-stage kidney disease (ESKD) worldwide and is caused by defective type 4 collagen due to pathogenic variants of COL4A3, COL4A4, or COL4A5. Type 4 collagen also exists in the eyes and ears, and thus ocular defects and hearing loss occur in AS. The understanding of AS has expanded over the past two decades due to greater availability of genetic testing and research on genotype-phenotype correlation. Patients previously diagnosed with idiopathic steroid resistant nephrotic syndrome or ESKD of unknown etiology may now be diagnosed as AS if pathogenic COL4A3-5 variants are identified. Some carriers of heterozygous COL4A3-5 variants may now be classified into females with X-linked AS or autosomal dominant AS, if there are typical pathologic changes in the glomerular basement membrane or if there is proteinuria and progression of kidney disease. Lastly, it has been recommended that renin-angiotensin-aldosterone system inhibition be started as soon as possible for selected AS patients for its long-term protective effect against kidney function deterioration. The purpose of this review is to introduce these important concepts to general pediatricians and pediatric nephrologists.